2006
DOI: 10.1093/nar/gkl737
|View full text |Cite
|
Sign up to set email alerts
|

Both introns and long 3′-UTRs operate as cis-acting elements to trigger nonsense-mediated decay in plants

Abstract: Nonsense-mediated mRNA decay (NMD) is a eukaryotic quality control mechanism that identifies and eliminates aberrant mRNAs containing a premature termination codon (PTC). Although, key trans-acting NMD factors, UPF1, UPF2 and UPF3 are conserved in yeast and mammals, the cis-acting NMD elements are different. In yeast, short specific sequences or long 3′-untranslated regions (3′-UTRs) render an mRNA subject to NMD, while in mammals' 3′-UTR located introns trigger NMD. Plants also possess an NMD system, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
253
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(264 citation statements)
references
References 63 publications
10
253
0
1
Order By: Relevance
“…Our data indicated that neither the existence of 39 UTR introns, nor intron location (beyond 50 to 55 bp downstream of the stop codon), nor intron length (over 300 nucleotides) was associated with enhanced uncapping of endogenous genes (see Supplemental Figures 8C and 8D online). Note that the latter two of these features are hallmarks for NMD as revealed by reporter transgenes (Kertesz et al, 2006;Kerenyi et al, 2008). Other 39 UTR structural features, namely, pseudoknots, GC contents, minimal free energy, and length, were also not clearly associated with enhanced uncapping (see Supplemental Figures 8E to 8H online).…”
Section: The 59 Untranslated Region Structure and Transcript Length Amentioning
confidence: 96%
“…Our data indicated that neither the existence of 39 UTR introns, nor intron location (beyond 50 to 55 bp downstream of the stop codon), nor intron length (over 300 nucleotides) was associated with enhanced uncapping of endogenous genes (see Supplemental Figures 8C and 8D online). Note that the latter two of these features are hallmarks for NMD as revealed by reporter transgenes (Kertesz et al, 2006;Kerenyi et al, 2008). Other 39 UTR structural features, namely, pseudoknots, GC contents, minimal free energy, and length, were also not clearly associated with enhanced uncapping (see Supplemental Figures 8E to 8H online).…”
Section: The 59 Untranslated Region Structure and Transcript Length Amentioning
confidence: 96%
“…Such reduction was not observed when a termination codon was introduced within or 6 nt upstream of the recognition site. Position of termination codons of major ORFs is critical for susceptibility of mRNAs to the nonsense-mediated mRNA decay system (Kertész et al, 2006). However, the pri-TAS2 mutant transcripts with altered position of ORF3 termination codon are unlikely targeted by the mRNA decay system because accumulation of the transcripts was not significantly affected by the mutations in the absence of miR173 overexpression (Supplemental Fig.…”
Section: Sde5 Acts On the Tas2 Cleavage Fragments Before Dsrna Synthementioning
confidence: 99%
“…eukaryotes that degrades mRNAs with a premature termination codon. In plants, mRNAs that have an extended noncoding distance between the premature termination codon and 39 end of the mRNA, or which have a downstream splice junction, are recognized by the NMD system and targeted for degradation (Kertesz et al, 2006;Hori and Watanabe, 2007;Kerenyi et al, 2008). To test whether HSFA2-II is subject to NMD, a T-DNA insertion mutant in the NMD machinery (upf1-5; Arciga-Reyes et al, 2006) was compared with wild-type plants for the induction of HSFA2 and HSFA2-II RNAs following heat or AZC treatment.…”
Section: Hsfa2-ii Rna Is Not Active and Is Degraded By Non-sense-medimentioning
confidence: 99%